The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1093/neuros/nyz351
|View full text |Cite
|
Sign up to set email alerts
|

Resting-State SEEG May Help Localize Epileptogenic Brain Regions

Abstract: BACKGROUND Stereotactic electroencephalography (SEEG) is a minimally invasive neurosurgical method to localize epileptogenic brain regions in epilepsy but requires days in the hospital with interventions to trigger several seizures. OBJECTIVE To make initial progress in the development of network analysis methods to identify epileptogenic brain regions using brief, resting-state SEEG data segments, without requiring seizure r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
67
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(73 citation statements)
references
References 31 publications
5
67
0
Order By: Relevance
“…15 We found that epileptogenic structures demonstrated higher connectivity than nonepileptogenic regions, and connectivity measures may predict epileptogenicity with modest accuracy. 15 Beyond small sample size, one limitation is that information may be lost using dichotomized regional classification, without considering other areas involved in seizure networks. 14,16 Although imaginary coherence is a linear measurement, 17 it is unknown if nonlinear, information theorybased connectivity may demonstrate improved accuracy in identifying epileptogenic regions.…”
Section: Introductionmentioning
confidence: 72%
See 2 more Smart Citations
“…15 We found that epileptogenic structures demonstrated higher connectivity than nonepileptogenic regions, and connectivity measures may predict epileptogenicity with modest accuracy. 15 Beyond small sample size, one limitation is that information may be lost using dichotomized regional classification, without considering other areas involved in seizure networks. 14,16 Although imaginary coherence is a linear measurement, 17 it is unknown if nonlinear, information theorybased connectivity may demonstrate improved accuracy in identifying epileptogenic regions.…”
Section: Introductionmentioning
confidence: 72%
“…Twenty-five patients with medically refractory focal epilepsy were included in this study, including 15 individuals from our prior study. 15 Patients had video monitoring and SEEG recordings obtained at Vanderbilt University Medical Center (VUMC) between 2017 and 2019. This investigation was approved by VUMC Institutional Review Board, and informed written consent was obtained from patients.…”
Section: Subjectsmentioning
confidence: 99%
See 1 more Smart Citation
“…In another study, alpha, theta, and delta imaginary coherence within a region and between regions was significantly higher in epileptogenic regions compared to non-epileptogenic regions, with the alpha-frequency band showing the biggest differences (29). Furthermore, several graph theory measures, including nodal betweenness centrality, edge betweenness centrality, and clustering coefficient were significantly higher in epileptogenic regions.…”
Section: Several Methods Have Been Used To Analyze the Functional Conmentioning
confidence: 89%
“…Given that the vast majority of intracranial recordings are in the interictal state, it would seem logical to try and utilize these ‘steady-state’ recordings for clinical localization ( Goodale et al , 2020 ), a concept that is supported at the neuronal level by animal literature showing interictal neuronal network abnormalities in animal models. Early work in interictal microelectrode recordings attempted to ascertain interictal properties of ‘epileptic’ and ‘nonepileptic’ neurons in the interictal state ( Ward and Schmidt, 1961 ; Isokawa-Akesson et al , 1987 , 1989 ), mainly in mesial temporal structures.…”
Section: The Future: Single-unit Recordings In the Clinical Contextmentioning
confidence: 99%